Undang-Undang Dan Kebijakan Pemerintah tentang Pendidikan Islam - Tine, Nurhayati (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
Based on the 1945 Constitution, all the Indonesian people deserve a decent education, as the government officials elected by the people charged to establish and conduct national education system. To carry out what is the mandate of the 1945 Constitution, the government is allowing the public to provide education through educational institutions run by government agencies or managed by private but still remain in government coordination. Consequences of the Government Regulation No. 55 of 2007 is required for parties of religious non-formal education have when students in excess of 15 people to report/ register with the Ministry of Religious district or city . This step is performed in order to obtain recognition of a more